2018
DOI: 10.1002/hpja.224
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of the midwifery initiated oral health‐dental service program: Perceptions of dental professionals

Abstract: Issue addressed All pregnant women should have a comprehensive oral health evaluation. Unfortunately, many pregnant women seldom seek dental care and some dentists are hesitant to treat during pregnancy. To address these issues, the Midwifery Initiated Oral Health Dental Service (MIOH‐DS) program was developed in Australia. The aim of this study was to undertake a process evaluation and explore the perceptions of dental professionals involved in the program to determine the acceptability, feasibility and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…However, despite this evidence, in Spain, as in other countries [ 41 , 42 , 43 ], the dental attendance of pregnant women is low, which has been attributed to multiple barriers [ 13 , 15 , 28 , 44 , 45 ], which were identified by participants in the current study (Items 54–64). Even though the approach to these barriers via the implementation of strategies of oral health promotion have contributed to improving the dental attendance of pregnant women [ 46 , 47 ], in Spain, unlike in other developed countries (for example, Australia) [ 48 , 49 ], the issue of maternal oral health during pregnancy continues to be a poorly assessed and treated aspect, which is almost exclusively managed by dentists, with minimum or zero participation from other healthcare professionals [ 8 , 10 ]. This could be due to the expert panels in charge of the development of Spanish clinical practice guidelines and clinical protocols intended for the attention to pregnant women by midwives being composed of gynecologists, obstetricians, pediatricians, general practitioners, psychiatrists, nurses, and midwives [ 10 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this evidence, in Spain, as in other countries [ 41 , 42 , 43 ], the dental attendance of pregnant women is low, which has been attributed to multiple barriers [ 13 , 15 , 28 , 44 , 45 ], which were identified by participants in the current study (Items 54–64). Even though the approach to these barriers via the implementation of strategies of oral health promotion have contributed to improving the dental attendance of pregnant women [ 46 , 47 ], in Spain, unlike in other developed countries (for example, Australia) [ 48 , 49 ], the issue of maternal oral health during pregnancy continues to be a poorly assessed and treated aspect, which is almost exclusively managed by dentists, with minimum or zero participation from other healthcare professionals [ 8 , 10 ]. This could be due to the expert panels in charge of the development of Spanish clinical practice guidelines and clinical protocols intended for the attention to pregnant women by midwives being composed of gynecologists, obstetricians, pediatricians, general practitioners, psychiatrists, nurses, and midwives [ 10 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is about people receiving the right care, at the right time, by the right professional and in the right place. A number of studies in this review also reported on evaluation outcomes from the implementation process, such as staff and/or patient experiences and/or satisfaction26 32 37 43 48 54 60 62 63 65 69 70 73 and facilitators and barriers to implementation 27 28 33 36 39 41 44 47 51 56 58 59 70 72 73. Harnagea et al , in their recent scoping review, provide a detailed report on the barriers and facilitators in the integration of oral healthcare into primary care,12 which are similar to the findings in this review and as such will not be discussed in detail.…”
Section: Discussionmentioning
confidence: 76%
“…The initial search resulted in the identification of 8731 unique articles, of which 213 were assessed for eligibility. On completion of the full text review, 49 studies describing various interventions were included in this review 25–73. List of studies excluded during the full text review, along with the reasons, is presented in online supplemental table S4.…”
Section: Resultsmentioning
confidence: 99%
“…In the authors’ local health area, an Early Childhood Oral Health Program integrates oral healthcare into general health interventions by child health professionals [ 83 , 84 ], and the surgical treatment of ECC in public hospitals requires attendance with an oral health therapist and dietitian in ECC prevention education. A midwifery-initiated oral health service with antenatal dental treatment in the Greater Western Sydney region of Australia improved maternal oral health knowledge, oral hygiene and health and the uptake of dental services, where the process evaluation reported positive experiences by midwives, dental health professionals and mothers [ 85 , 86 , 87 ]; further, it has since developed state government prenatal oral health resources, been adopted into a policy in the state of Victoria, and been integrated into the national body of midwifery’s continuing education program [ 88 , 89 ]. Similarly, the Healthy Tums Healthy Gums program, delivered by social workers, oral health staff and dietitians to vulnerable families, improved oral health and childhood nutrition knowledge, including cup use from 6 months onwards, the cessation of bottle use by 12 months of age, and identifying cariogenic and non-cariogenic foods and drinks [ 90 ].…”
Section: Discussionmentioning
confidence: 99%